Analysis of the Influence of Cyclone Structure Characteristics on Combustion Chamber Performance. (July 2020) - Xiang, Wenwei; Liu, Jiang; Weng, Peifen; Fu, Zaiguo
Abstract: The cyclone is an important part of the combustion chamber of the gas turbine and has a direct impact on the combustion performance in the combustion chamber. Therefore, it is of great value to study the structural characteristics of the cyclone. This paper firstly analyses the structural characteristics of cyclone that have the greatest impact on the performance of the combustion chamber through the relevant data and the structural parameters of the actual combustion chamber. Then appropriately simplifies the structure of the combustion chamber, designing a F-class combustion chamber with cyclone. Numerical simulation method is compared with the actual combustion chamber data to verify whether the design of the cyclone meets the requirements, thus preliminary determining the blade installation structure and the number of blades of the combustion chamber cyclone. In the end, using the model combustion chamber as a blueprint, adjust the blade characteristics of the cyclone for different installation angles (40°, 45°, and 50°) and the number of blades (6, 8, and 10). The combustion chamber model is simulated to determine that the flow field of the combustion chamber is the best when the angle is 45°and the number of blades is 8.